Produktive Financing Problems in Islamic Banks, (Research at Universities in Indonesia : A Systematic Literature Review Analysis) - Komarudin , Parman; Hadi , Hendra; Sodiki , Muhammad (LPPPM STAI Darul Hikmah Bangkalan, 2023)
This research is a systematic literature review study that aims to find out the extent of research conducted by students in Indonesia regarding the Problems of Productive Financing in Islamic Banks with an emphasis on preparing final assignments such as Theses and Dissertations. The method used consists of three stages, namely collection, assessment, and presentation. The results of this study indicate that there are 16 final assignments that address the problem of Productive Financing Problems in Islamic Banks in universities throughout Indonesia. The writing of this final project has been started since 2018 and will reach its peak in 2022. Of the many tertiary institutions in Indonesia, students of the Raden Intan Lampung State Islamic University and Iain Padangsidimpuan are the most enthusiastic in making Productive Financing Studies on Islamic Banks in their final project. The most widely used method is the quantitative method with a total of 8 pieces of research and 7 qualitative pieces and the theme most widely raised is related to the analysis and influence of Earning Financing Assets. Until now, studies on Productive Financing in Islamic Banks in tertiary institutions in Indonesia have concluded that Productive Financing (profit sharing system) in Islamic banks is still low and less desirable than consumptive financing. From year to year the profit value in Islamic banking has a decreasing effect. Some of the problems faced in the development of productive financing are not only external but also internal factors from the Islamic banking itself. Some of them are the risks that are considered high, the lack of supervision process, the understanding and interest of the public which is still small in the perception of sharia financing, the inadequate quality and number of human resources, profit-sharing financing is considered complicated and inefficient, the lack of innovation and service development compared to conventional banks and so on. regulations and the role of the government which are considered not optimal. Â Keywords: Problems, productive financing, Islamic banking, Systematic Literature Review Analysis